2009
DOI: 10.1039/b901069f
|View full text |Cite
|
Sign up to set email alerts
|

A completely anoxic microbial fuel cell using a photo-biocathode for cathodic carbon dioxide reduction

Abstract: Typical microbial fuel cells (MFCs) rely on precious metals for reduction of oxygen at the cathode, but recently MFCs have been developed that use biocathodes for power generation with alternate electron acceptors. It is shown here that with illumination it is possible to develop a biocathode that uses dissolved carbon dioxide (bicarbonate) as the acceptor. During acclimation, the cathode was set at a potential of 0.242 V (vs. SHE) using a potentiostat. After approximately one month of acclimation, a current o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(62 citation statements)
references
References 16 publications
2
60
0
Order By: Relevance
“…BESs with microorganisms at the bioanode or biocathode generally may be combined with any other known bio or chemical half-reaction at the other electrode ). Recently, MFCs were developed with mediatorless biocathodes using various final electron acceptors like oxygen (Bergel et al 2005), nitrate (Clauwaert et al 2007a), or CO 2 (Cao et al 2009). The last years, BES research has also moved in the direction from producing electricity in MFCs to MEC applications using microorganisms as novel biocatalysts that produce all kinds of value added products like H 2 (Rozendal et al 2006b), CH 4 ), H 2 O 2 ), or ethanol (Steinbusch et al 2009), while using final electron acceptors like protons, CO 2 , and acetate.…”
Section: Introductionmentioning
confidence: 99%
“…BESs with microorganisms at the bioanode or biocathode generally may be combined with any other known bio or chemical half-reaction at the other electrode ). Recently, MFCs were developed with mediatorless biocathodes using various final electron acceptors like oxygen (Bergel et al 2005), nitrate (Clauwaert et al 2007a), or CO 2 (Cao et al 2009). The last years, BES research has also moved in the direction from producing electricity in MFCs to MEC applications using microorganisms as novel biocatalysts that produce all kinds of value added products like H 2 (Rozendal et al 2006b), CH 4 ), H 2 O 2 ), or ethanol (Steinbusch et al 2009), while using final electron acceptors like protons, CO 2 , and acetate.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these adaptations utilize photosynthetic processes only at the biofilm anode, such as photosynthetic generation of hydrogen or photosynthetically derived electrons for electricity generation (5)(6)(7). Few studies have focused on photosynthetic processes at the biofilm cathode (1,(8)(9)(10). For example, He et al (8), reported on the self-assembly of a synergistic phototrophicheterotrophic cathode biofilm from a sediment microbial fuel cell (SMFC) (a microbial fuel cell comprised of an organic-matteroxidizing anode embedded in anoxic marine sediment and an oxygen-reducing cathode positioned in overlying oxic water [11,12]).…”
mentioning
confidence: 99%
“…Carbon dioxide reduction in the cathodic chamber is a relatively new concept. Microalgae 3 and photosynthetic bacteria 6 have been used successfully as catalysts in the cathodic chamber. The former is used with methylene blue as a mediator, while the latter is grown as a biofilm and no electron mediator is used.…”
Section: Introductionmentioning
confidence: 99%